Environmental controls on the growth, photosynthetic and calcification rates of a Southern Hemisphere strain of the coccolithophore Emiliania huxleyi - Feng, Y; Roleda, MY; Armstrong, E; Philip Boyd; Catriona Hurd (2017)
We conducted a series of diagnostic fitness response experiments on the coccolithophore, Emiliania huxleyi , isolated from the Subtropical Convergence east of New Zealand. Dose response curves (i.e., physiological rate vs. environmental driver) were constructed for growth, photosynthetic, and calcification rates of E. huxleyi relative to each of five environmental drivers (nitrate concentration, phosphate concentration, irradiance, temperature, and p CO 2 ). The relative importance of each environmental driver on E. huxleyi rate processes was then ranked using a semi-quantitative approach by comparing the percentage change caused by each environmental driver on the measured physiological metrics under the projected conditions for the year 2100, relative to those for the present day, in the Subtropical Convergence. The results reveal that the projected future decrease in nitrate concentration (33%) played the most important role in controlling the growth, photosynthetic and calcification rates of E. huxleyi , whereas raising p CO 2 to 75 Pa (750 ppm) decreased the calcification : photosynthesis ratios to the greatest degree. These findings reveal that other environmental drivers may be equally or more influential than CO 2 in regulating the physiological responses of E. huxleyi , and provide new diagnostic information to better understand how this ecologically important species will respond to the projected future changes to multiple environmental drivers.